Modulation of type 1 cannabinoid receptor activity by cannabinoid by-products from Cannabis sativa and non-cannabis phytomolecules - Zagzoog, Ayat; Cabecinha, Ashley; Abramovici, Hanan; Laprairie, Robert B. (Frontiers in Pharmacology, 2022)
Cannabis sativa contains more than 120 cannabinoids and 400 terpene compounds (i.e. phytomolecules) present in varying amounts. Cannabis is increasingly available for legal medicinal and non-medicinal use globally, and with increased access comes the need for a more comprehensive understanding of the pharmacology of phytomolecules. The main transducer of the intoxicating effects of Cannabis is the type 1 cannabinoid receptor (CB1R). ∆9-tetrahydrocannabinolic acid (∆9-THCa) is often the most-abundant cannabinoid present in many cultivars of Cannabis. Decarboxylation converts ∆9-THCa to ∆9-THC, which is a CB1R partial agonist. Understanding the complex interplay of phytomolecules – often referred to as ‘the entourage effect’ – has become a recent and major line of inquiry in cannabinoid research. Additionally, this interest is extending to other non-Cannabis phytomolecules, as the diversity of available Cannabis products grows. Here, we chose to focus on whether ten phytomolecules (∆8-THC, ∆6a,10a-THC, 11-OH-∆9-THC, cannabinol, curcumin, epigallocatechin gallate, olivetol, palmitoylethanolamide, piperine, and quercetin) alter CB1R-dependent signaling with or without a co-treatment of ∆9-THC. Phytomolecules were screened for their binding to CB1R, inhibition of forskolin-stimulated cAMP accumulation and arrestin2 recruitment in Chinese hamster ovary cells stably-expressing human CB1R. Select compounds were assessed further for cataleptic, hypothermic, and anti-nociceptive effects in male mice. Our data reveal partial agonist activity for the cannabinoids tested, as well as modulation of ∆9-THC-dependent binding and signaling properties of phytomolecules in vitro and in vivo. These data represent a first step in understanding the complex pharmacology of Cannabis and non-Cannabis derived phytomolecules at CB1R and determining whether these interactions may affect the physiological outcomes, adverse effects and abuse liabilities associated with the use of these many compounds.